An improved method for the preparation of 2-hydrazinylbenzo[d]thiazoles from benzo[d]thiazol-2-amines (Indian Journal of Chemistry (IJC), 2024)
2-Hydrazinylbenzo[d]thiazoles were prepared by reacting benzo[d]thiazol-2-amines with hydrazine hydrate in presence of water and hydrochloric acid. The developed method is cost effectiveand viable compared to previous approach